PENGARUH JENIS FLUIDA TERHADAP UNJUK KERJA MINIATUR PEMBANGKIT LISTRIK TENAGA UAP - Wahidah, Nurul; Ihsan, Ihsan; Zelviani, Sri; Abadi, Firdaus Alam (JFT: Jurnal Fisika dan Terapannya, 2019)
The Research has been conducted which aims to determine the type of fluid on the power generated in the Miniature (PLTU) Steam Power Plant. The results obtained show that the turbidity level of water in aquades is 0.0 NTU, the turbidity level in 1.2 NTU well water and the turbidity level in river water is 6.5 NTU, with the concentration of acidity in aquades 5.6, at water concentrations wells 5.5 and at river water concentrations 5.2. COD content in aquades 63.2 mg / L, in well water 110.6 mg/L, in river water 189.6 mg / L, BOD content in aquades 2.2 ppm, in well water 1.1 ppm, and at 0.2 ppm river water based on the results of research that has been done can be concluded that the type of fluid influences the amount of electric power generated in the sample aquades 0.021 watts, in well water 0.006 watts, in river water 0.004 watts.